Enzyme-instructed hybrid nanogel/nanofiber oligopeptide hydrogel for localized protein delivery - Tianyue Jiang; Yudi Ma; Xiao Xu; Qingchun Ji; Mingxing Feng; Cheng Cheng; Yang Feng; Bingfang He; Ran Mo (Elsevier, 2021)
Enzyme-catalysis self-assembled oligopeptide hydrogel holds great interest in drug delivery, which has merits of biocompatibility, biodegradability and mild gelation conditions. However, its application for protein delivery is greatly limited by inevitable degradation of enzyme on the encapsulated proteins leading to loss of protein activity. Moreover, for the intracellularly acted proteins, cell membrane as a primary barrier hinders the transmembrane delivery of proteins. The internalized proteins also suffer from acidic and enzymatic degradation in endosomes and lysosomes. We herein develop a protease-manipulated hybrid nanogel/nanofiber hydrogel for localized delivery of intracellularly acted proteins. The embedded polymeric nanogels (CytoC/aNGs) preserve activity of cytochrome c (CytoC) that is an intracellular activator for cell apoptosis as a model protein against proteolysis, and do not affect the gelation properties of the protease-catalysis assembled hydrogels. The injectable hydrogel (CytoC/aNGs/Gel) serves as a reservoir to enhance intratumoral retention and realize sustainable release of CytoC/aNGs. The released CytoC/aNGs increase cellular uptake of CytoC and enhance its intracellular delivery to its target site, cytoplasm, resulting in favorable apoptosis-inducing and cytotoxic effects. We show that a single local administration of CytoC/aNGs/Gel efficiently inhibit the tumor growth in the breast tumor mouse model.